CULTURAL IDENTITY MANAGEMENT THROUGH DIGITAL ART TOOLS - Swain, Biswaranjan; Panda, Sourav; Bhatnagar, Sanjay; Anitha Josephine; Sarna, Shilpi; Sharma, Varun Kumar; Bhanuse, Vijaykumar (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The quick development of digital artistic means has changed the way people and societies build, communicate and maintain cultural identity in networked space. With the rise of digital humanities and cultural informatics, artistic practices are becoming more and more involved with virtual spaces, in which identity is a hybrid, fluid, and collaboratively constructed space. The proposed study explores how digital illustration, 3D modeling, immersive media, and AI-assisted creative systems are changing to allow culturally-informed self-representation. The study gathers information based on digital artists, cultural communities, and online creative platform through a mixed-method approach that merges qualitative knowledge and analysis of digital artifacts. The theoretical background unites the theory of identity construction, digital heritage and transcultural hybridity models to explore the process of digital art tools mediating cultural narratives. The results show that digital technologies enable artists to bargain identity between the conventional and modern experience, providing the opportunity to reinterpret the heritage motifs, rethink the folklore, and reinforce the diasporic connections. The examples of community-based programs like collaborative archives, open-source cultural libraries, and participatory storytelling show that digital platforms help to keep the cultural memory in a dynamic form.